Secondary Tropical Dry Forests Are Important to Cattle Ranchers in Northwestern Costa Rica - Godinot, Florent (2020)
[Introduction]: In the dry regions of Central America, forests in cattle ranches are used as a refuge for cattle during the dry season, and there is no much information about this practice. [Objective]: to determine the frequency of this practice and how it fits in farm management. [Methodology]: We conducted semi-structured interviews with cattle ranchers in 43 farms in Liberia County, Guanacaste, Costa Rica. [Results]: Cattle farmers suffered from the loss of profitability due to droughts, fire, and cattle theft. Cattle browsing in the forest was used by 70 % of farms, mostly between March and May. No type of farm or feeding strategy was associated with forest browsing. The high variability in farm management did not provide a distinct classification of feeding strategies. We found a difference in farm structure and feed types between ranches in the plains and mountain slopes. The decision to use forests for browsing seemed to rely on a trade-off between animal welfare and ease of management. Traditional knowledge about cattle behavior in forests was variable and often limited to forest edges and pastures. [Conclusions]: This research shows that forests should be taken into consideration when analyzing cattle ranching in dry regions of Central America. We recommend a further study on feeding strategies and the impact of cattle on forest integrity to determine if agricultural policymakers should foster these low-costs alternatives.